Sosialisasi Jerat Pergaulan Bebas Di SMK Negeri 1 Tanara - Aan, Aan; Saripudin, Saripudin; Hidayat, Muhammad Hilman; Panjaitan, Rosdewana; Nuryati, Nuryati; Dewi, Maulani; Syarkawi, Syarkawi (Amirul Bangun Bangsa, 2025)
Sosialisasi bertema